Synthesis and Antimicrobial Activity of Some New 2-(3´ -Phenoxy Phenyl)- 3-Aryl-5-Methyl-4-Thiazolidinones - Solankee, Anjani; Patel, Jayesh; Kapadia, Kishor; Thakor, Indrajit; Upadhyay, Ketki (Asian Journal of Chemistry, 2010)
2-(3´-Phenoxy phenyl)-3-aryl-5-methyl-4-thiazolidinones (IIa–w) have been synthesized by the cyclocondensation of thiolactic acid with Schiff bases (Ia–w) which in turn were prepared by the action of m-phenoxy benzaldehyde with aryl amines. The structures of the synthesized compounds have been confirmed by elemental analysis. IR and 1H NMR spectral data. All the products were evaluated for their in vitro growth inhibitory activity against several microbes like Staphylococcus aureus, Escherichia coli, Bacillus subtilis, Serratia marcescens, Proteus vulgaris and Pseudomonas aeruginosa.